Development and evaluation of formal guidelines for donor selection for human milk banks. (4th May 2020) - Clifford, Vanessa; Sulfaro, Christine; Lee, June; Pink, Joanne; Hoad, Veronica
Abstract : Aim: Donor selection for milk banks is essential to ensure the safety and nutritional quality of the donor milk, and to ensure that the prospective donor and her breastfeeding infant do not come to harm through donating. Australian Red Cross Lifeblood Milk went through a robust process to develop a set of criteria for the selection and screening of potential breast milk donors, which included development of a Donor Questionnaire (DQ), supported by a formal set of Guidelines for the Selection of Milk Donors. Key screening questions from the DQ were made available to prospective donors to self‐screen prior to the formal assessment process. The aim of this study was to review the outcomes of milk donor screening at Lifeblood Milk. Methods: We reviewed the outcomes of our donor screening process over the first 12‐months (July 2018–June 2019) of operations. Results: A total of 50 out of 327 donors who responded to the self‐screening questions were not able to proceed further; 201 donors were formally screened using the DQ and Guidelines for the Selection of Milk Donors, with 9 of 201 deferred based on their responses. An additional two donors were deferred (failed phlebotomy ( n = 1) and reactive infectious disease serology ( n = 1)), with 190 of 201 (95%) of prospective donors accepted after screening. Conclusions: Our experience highlighted international differences in practice between milk banks and lack of strong research to inform milk donor selection. Making a set of key screening questions available to donors for self‐screening resulted in a high acceptance rate (95%) for donors who began the formal screening process. Further work is needed to better understand the impact of deferral on prospective milk donors.